Segregation of parallel inputs to the anteromedial and anteroventral thalamic nuclei of the rat - O'MARA, SHANE (My University, 2013)
Many brain structures project to both the anteroven tral thalamic nucleus and the anteromedial thalamic nucleus. In the present stud y, pairs of different tracers were placed into these two thalamic sites in the same rats to determine the extent to which these nuclei receive segregated inputs. Only input s from the laterodorsal tegmental nucleus, the principal extrinsic cholinergic source for these thalamic nuclei, showed a marked degree of collateralisation, with approximat ely 13% of all cells labelled in this tegmental area projecting to both nuclei. Elsewher e, double labelled cells were very scarce, comprising ~1% of all labelled cells. Three general patterns of anterior thalamic innervation were detected in these other a reas. In some sites, e.g., prelimbic cortex, anterior cingulate cortex, and secondary mo tor area, cells projecting to the anteromedial and anteroventral thalamic nuclei were closely intermingled, with often only subtle distribution differences. These same pr ojections were also often intermingled with inputs to the mediodorsal thalami c nucleus, but again there was little or no collaterisation. In other sites, e.g., the subiculum and retrosplenial cortex, there was often less overlap of cells projecting to the two anterior thalamic nuclei. A third pattern related to the dense inputs from the medial mammillary nucleus, where well defined topographies ensured little intermingling of the neurons that innervate the two thalamic nuclei. The finding, that a very small minority of cortical and limbic inputs bifurcate to innervate both anterior thalami c nuclei, highlights the potential for parallel information streams to control their functions, despite arising from common regions.
PUBLISHED
Keywords: cingulate cortex; hippocampus; Neuroscience; Behavioral/Experimental Psychology